BRCA1-A and LIG4 complexes mediate ecDNA biogenesis and cancer drug resistance - Oliver W. Chung; Shun Yao; Ling Wang; Fu Yang; Lauren Schier; Melissa Aldana; Christian Cerda-Smith; Haley M. Hutchinson; Kris C. Wood; Weijia Su; Mustafa Khasraw; Lee Zou; et al. (Proceedings of the National Academy of Sciences, 2026)
Extrachromosomal circular DNA (ecDNA) is frequently generated within the nucleus, contributing to genome dynamics and heterogeneity, thereby promoting cancer cell evolution and adaptation. However, the mechanisms underlying ecDNA biogenesis remain poorly understood. Here, using genome-wide CRISPR screening in human cells, we identified the BRCA1-A and the LIG4 complexes as key drivers of ecDNA production. Following DNA segmentation, the upstream BRCA1-A complex protects DNA ends from excessive resection, promoting end-joining for circularization. Conversely, the MRN complex, which mediates end resection and thus antagonizes the BRCA1-A complex, suppresses ecDNA formation. Downstream, LIG4 conservatively mediates ecDNA production by joining the free ends of the DNA fragments. Furthermore, ecDNA from patient tumors harbors junction sites with a LIG4 signature. Notably, disruption of either LIG4 or the BRCA1-A complex in cancer cells impairs ecDNA-mediated adaptation, hindering the development of resistance to both chemotherapy and targeted therapies. Together, our study reveals the roles of the LIG4 and BRCA1-A complexes in ecDNA biogenesis, and uncovers therapeutic targets to block ecDNA-mediated adaptation for cancer treatment.